Energy subsidy and oil price fluctuation, and price behavior in Malaysia:A time series analysis - Dzul Hadzwan, Husaini; Puah, Chin Hong; Lean, H.H (Elsevier Ltd, 2019)
Balancing between favorable energy subsidy and the financial burden of government is crucial for policymakers. This article intends to advance this thinking by informing policymakers about how price reacts to changes in the international oil price and energy subsidy program. Hence, it is essential to investigate the empirical evidence concerning the relationship between the international oil price and energy subsidy, and price behavior. This study used time series data covering the period 1981–2015 to explore the price behavior on energy subsidy rationalization and oil price fluctuation in Malaysia. To prepare concrete empirical evidence, we employed the autoregressive distribution lag (ARDL) approach to capture the long-run dynamic behavior. Our findings indicated that both factors, oil price and energy subsidy, are significant in influencing the pattern of price behavior. The PPI (Producer Price Index) was more sensitive to changes in the oil price than the CPI (Consumer Price Index). The PPI was found to be affected more while the CPI was less affected. We call on policymakers to provide the Malaysian economic system with a productive social safety net to offset the negative impact caused by energy subsidy reform.